A COMMON MECHANISM UNDERLYING APATHY ACROSS NEUROLOGICAL DISORDERS. Issue 12 (15th November 2016) - Heron, Campbell Le; Manohar, Sanjay; Muhammed, Kinan; Drew, Dan; Blake, Annie; Jackson, Matthew; Husain, Masud
Abstract : Apathy is a common, debilitating syndrome characterized by lack of motivation and inactivity, which significantly reduces quality of life across a range of brain disorders. We investigated whether hypersensitivity to effort or insensitivity to rewards might underlie the apathetic state when people make effort-based decisions. Using a novel task that manipulated reward and effort independently, participants (N=72, 24 each apathetic patients, non-apathetic patients, healthy controls) decided whether to engage with offers of monetary reward for physical effort. Patients included individuals with a range of diagnoses: cerebral small vessel disease and CADASIL, Parkinsonian conditions and limbic encephalitis. Apathy was defined using the Lille apathy rating scale. Apathetic patients accepted significantly fewer offers than non-apathetic patients, who did not differ from controls. This difference in behaviour was mainly driven by insensitivity to rewards rather than hypersensitivity to effort, confirmed using computational modelling, and with effects similar across diagnoses. Further investigation in the CADASIL group revealed reward insensitivity was associated with blunted autonomic (pupillary) responses to incentives. These findings demonstrate effort-based decision-making is disrupted in patients with apathy. They provide a plausible mechanism for the reduced goal-directed behaviour and state of inactivity that characterises the syndrome, and identify a potential therapeutic avenue.